Private Solutions for Infrastructure in Cambodia : A Country Framework Report - Public-Private Infrastructure Advisory Facility (Washington, DC: World Bank, 2013)
Infrastructure plays a crucial role in supporting Cambodia's growth and development. Improving access to efficient and affordable water, electricity, transport, and telecommunications services has a major impact on the living standards of individual households. This Country Framework Report (CFR) is one of a series of country reviews aimed at improving the environment for the private sector involvement in infrastructure. This book describes and evaluates the current status and performance of key infrastructure sectors and the policy, regulatory, and institutional environment for involving the private sector in infrastructure sectors. It also helps policymakers to establish future reform and development strategies.